The risk assessment of roof truss structure in Malaysia due to windstorm - Che Ku Mohd Shahidan, Che Ku Mohd Yusof (2015)
Recently the pattern of wind in Malaysia is unpredictable which there are increasing the number of damage and injuries due to wind hazard. The most possibility risk of wind load damage to buildings structure in particularly roof structure. Roof structure is form of roof trusses and roof coverings. The durability of the roof structure is closely related to material selection and design process. Fortunately in Malaysia, there are many options to get the good material to build roof trusses either wooden or steel. However, there is some weakness in the design process where engineer only consider the wind acts as downward pressure to roof structure. Pervious study had shown that the wind loads are not only act in downward pressure but it also act in uplift force which is caused by suction pressure. Therefore, this study will discuss the risk possibility of roof truss in Malaysia due to windstorm. A typical roof truss system is evaluated due to various wind effect which is wind pressure, wind suction and simultaneous of wind pressure and suction at the same time. From the result, it clearly shows that the roof truss structure failed at wind suction effect and simultaneous wind pressure and wind suction effect Therefore, there is lack of the wind effects consideration during design process due to poor knowledge about the wind hazard that caused the failure of roof structure.